Radical Ambition : C. Wright Mills, the Left, and American Social Thought - Geary, Daniel (Book collections on Project MUSE., 2009)
Sociologist, social critic, and political radical C. Wright Mills (1916-1962) was one of the leading public intellectuals in twentieth century America. Offering an important new understanding of Mills and the times in which he lived, Radical Ambition challenges the captivating caricature that has prevailed of him as a lone rebel critic of 1950s complacency. Instead, it places Mills within broader trends in American politics, thought, and culture. Indeed, Daniel Geary reveals that Mills shared key assumptions about American society even with those liberal intellectuals who were his primary oppo.